2020
DOI: 10.1515/nanoph-2020-0330
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spatiotemporal tracking of nano-objects diffusing in water-filled optofluidic microstructured fiber

Abstract: Three-dimensional (3D) tracking of nano-objects represents a novel pathway for understanding dynamic nanoscale processes within bioanalytics and life science. Here we demonstrate 3D tracking of diffusing 100 nm gold nanosphere within a water-filled optofluidic fiber via elastic light scattering–based position retrieval. Specifically, the correlation between intensity and position inside a region of a fiber-integrated microchannel has been used to decode the axial position from the scattered intensity, while im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Most recently, we have demonstrated particle separation and counting in an uninterrupted flow through a fiber device 31 . Furthermore, structured hollow core fibers allow for the guiding of light directly in the fluid media, which has been used for Raman sensing 32 and for the tracking of diffusion of nanoscale objects 33 , 34 including virus particles 35 . Structured optical waveguides, such as light cages, have been developed for absorption spectroscopy with possible applications in bioanalytics 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, we have demonstrated particle separation and counting in an uninterrupted flow through a fiber device 31 . Furthermore, structured hollow core fibers allow for the guiding of light directly in the fluid media, which has been used for Raman sensing 32 and for the tracking of diffusion of nanoscale objects 33 , 34 including virus particles 35 . Structured optical waveguides, such as light cages, have been developed for absorption spectroscopy with possible applications in bioanalytics 36 .…”
Section: Introductionmentioning
confidence: 99%
“…For our experiments, the offset obtained from fitting is À8.11 .110 À16 m 2 (entire dataset and N lag ¼ 2), which is in agreement with the theoretical prediction (À2D f t e /3 ¼ À7.96 Â 10 À16 m 2 ). Note that the nanosphere is actually never lost, that is, is present in all frames of the representative dataset, allowing to straightforwardly apply the MSD analysis reported in the study by Jiang et al [14] (more details can be found in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Here, it is important to note that the transverse confinement provided by the nanofluidic channel leads to a confined diffusion [25,26] through an increased viscosity, also hindering the diffusion along the longitudinal direction because of the liquid's high bulk modulus. This effect is included here by the so-called average resistance factor R avg , leading to the corrected diffusion constant D c ¼ D f =R avg [14,27] (more details on the resistance factor can be found in the Supporting Information and in the study by Jiang [14] ). The error of the fitted slope of the MSD (Equation ( 1)) defines the precision of the retrieved diffusion D f and hydrodynamic diameter d h and depends on the number of frames N c .…”
Section: Msd Analysismentioning
confidence: 99%
See 2 more Smart Citations